A Novel Method for Densification of Titanium Using Hydrogenation-Induced Expansion under Constrained Conditions. (15th March 2022) - Zhou, Chengshang; Lin, Fangrui; Sun, Pei; Chen, Zoujun; Duan, Zhongyuan; Zhu, Xianzhi; Liu, Yong; Fang, Zhigang Zak
Abstract: Full density of sintered Ti alloys is difficult to achieve through conventional pressureless sintering techniques. This paper introduces a novel approach for densifying powder metallurgy Ti alloys through constrained hydrogenation assisted densification (CHAD). This method utilizes hydrogenation-induced volumetric expansion and constrains a sintered Ti body in a rigid mold to achieve densification. The results demonstrate that the residual porosity in powder metallurgy CP-Ti and Ti-6Al-4V alloys can be effectively reduced or removed by CHAD, leading to improved tensile properties. The described method can be used as an efficient and cost-effective technique to make Ti and Ti alloys with high density and improved mechanical properties. Graphical Abstract: Image, graphical abstract